Writing Sri Lanka : literature, resistance and the politics of place - Salgado, Minoli (2007)
"Focusing on ways in which cultural nationalism has influenced both the production and critical reception of texts, Minoli Salgado offers a detailed analysis of eight leading Sri Lankan writers - Michael Ondaatje, Romesh Gunasekera, Shyam Selvadurai, A. Sivanandan, Jean Arasanayagam, Carl Muller, James Goonewardene and Punyakante Wijenaike - and challenges the theoretical, cultural and political assumptions that pit 'insider' against 'outsider', 'resident' against 'migrant', and the 'authentic' against the 'alien'. By interrogating the discourses of territoriality and boundary marking that have come into prominence since the start of the civil war, Salgado works to define a more nuanced and sensitive critical framework that actively reclaims marginalised voices, and draws on recent studies in migration and the diaspora to reconfigure the Sri Lankan critical terrain."--Jacket.
Errata sheet enclosed.
Keywords: 1900 - 2099; Sri Lankan literature (English) -- History and criticism; Politics and literature -- Sri Lanka -- History -- 20th century; Politics and literature -- Sri Lanka -- History -- 21st century; Politics and literature; Sri Lankan literature (English); Literatur; Sri Lanka; Englisch; Sri Lanka; Criticism, interpretation, etc; History